Ética e direitos humanos: princípios educacionais para uma sociedade democrática - Ahlert, Alvori (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The present research argues the urgency of the ethics as bedding for the search of a democratic society and its relations with the reflection on the human rights. Importance of the human rights for the construction of a democratic and effectively participation society and the directions of the democracy in the present time is argued it for which the human rights of third and fourth generations if constitute as basic premises for the exercise of the democratic citizenship.